Elucidating the dynamic of drought tolerance rice, MR219-4 to the Xanthomonas oryzae infection - Hani Shafiqah Shamsudin,; Muhammad Asyraf Muhammad Yaman,; Aziz Ahmad,; Muhamad Fairus Noor Hassim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Rice (Oryza sativa) is a primary source of food for more than half of the world’s population. Despite its importance, rice production struggles with various pathogenic attacks particularly by Xanthomonas oryzae that causes bacterial blight. Overcoming this issues is of utmost priority especially when the use of drought-tolerant varieties to secure production in erratic climate is on the rise. Thus it is important to comprehend the pathogenicity of this proteobacteria towards rice. Consequently this study was conducted to determine the pathology of X. oryzae infection on drought tolerance rice variety namely MR219-4 grown under normal conditions. 16-days old seedlings were infected with the pathogen and subsequently the morphological traits, total oil content and the variance between total oil, biomass (except for day 20) and dry weight of the infected and non infected plants were assessed in three developmental phases; seedlings, vegetative and reproductive. The results showed that plant height, root length, biomass and total oil content did not significantly differ between the infected and the control plants. However, variance analysis shows that bacterial infection caused a deterministic toward stochastic response in total oil/biomass variance over growth stages. Thus indicating that the population dynamic of MR219-4 defence mechanism to the infection is deterministic during the seedling stages and becoming stochastic during the vegetative phase paddy.